Analysis of the Development of Physical Qualities Characteristic of School Students' Static Activities - Shovkat Mukhamedjanov (Indonesian Journal of Sport, Health and Physical Education Science, 2025)
The aim analysis of the development of physical qualities characteristic of static activities of students of grades 5-7 consists in learning. A number of scientific sources on the impact of static exercises on the body of school-age children, the development of physical qualities characteristic of their static activities, and the possibility of using static exercises in physical education lessons to achieve high results in improving work capacity has analyzed. The relative growth in the 5th grade of the experimental group was 13.05%, while in the control group it was 6.24%. In the 6th grade, the relative growth in the experimental group was 14.26%, and in the control group it was 6.59%. In the 7th grade, the relative growth in the experimental group was 16.10%, and in the control group it was 7.25%. At the end of the experiment, static endurance increased more in 6th-grade students - by 2.99 s, in 7th-grade students - by 2.54 s, and in 5th-grade schoolchildren, this indicator changed by a small amount - by 2.31 s. The relative growth was 15.28% in 5th-grade students in the experimental group, and 5.42% in the control group. In the 6th grade of the experimental group, it was 15.70%, and in the control group it was 5.32%. In the 7th grade of the experimental group, it was 17.03%, and in the control group it was 6.39%. Among the indicators that grew during the pedagogical experiment, the most reliable result was related to static endurance.